Distribution and diversity of Meiobenthos in southern Caspian Sea (Mazandaran-Iran) - Zarghami, Maryam; Fatemi, Mohammad R.; Al-Maliky, Tariq H.; Mollayousefi, Masoomeh S.; Nazarhaghighi, Fatemeh (Mesopotamian Journal of Marine Sciences, 2019)
Biodiversity and distribution of benthic Meiobenthos in the sediments of the Southern Caspian Sea were studied in order to introduce and determine their relationship with the environmental factors. From 12 stations (ranging in depths from 5, 10, 20 and 50 meters), sediment samples were gathered for four seasons (2012). Temperature, salinity, dissolved Oxygen and pH were measured during sampling with CTD (conductivity, temperature and Depth). Percentage grain size and total organic matter and calcium carbonate were measured. The average water temperature ranged from 9.52 to 23.93 ͦC, dissolved Oxygen from 7.71 to 10.53 mg/L, salinity from 10.57±0.07 to 10.75±0.04 ppt., pH from 7.44±0.29 to 7.41±0.22, EC from 17.97±0.12 to 18.30±0.04 μs/cm2, TDS from 8.92±0.04 to 9.14±0.02 mg/L, total organic matter from 5.83±1.43 to 6.25±0.97% and calcium carbonate fluctuated from 2.36±0.36 to 1.68±0.19%. From the 4 groups of animals (Foraminifera, Crustacea, Worms and Mollusca), 40 species belonging to 29 genera of 25 families were identified Ammonia beccarii caspica, was the common species in all sampling stations. Depth was an important factor in the distribution of meiobenthos. Mean of maximum and minimum Shannon index were measured at depth of 5m and 50 m and were in the order of 0.93 and 0.43, respectively. Account of Shannon and Peilou’s index showed that this area is under pressure and is not steady.